Intermittent High Grade AV-Block and Atrial Flutter Associated with Lyme Carditis: : A Case Report - Abdelrahman, Ahmad; Alharbi, Abdulmajeed; Nesheiwat, Zeid; Grande, Robert (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.